PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS AUDIOVISUAL POWTOON DALAM MODEL PEMBELAJARAN KOOPERATIF TERHADAP HASIL BELAJAR FISIKA SISWA KELAS VIII MTS NEGERI 1 PALU - Oktavia , Rini; Syamsu (Universitas Tadulako, 2022)
This research aims to find out whether or not the influence of the use of Powtoon audiovisual-based learning media in the cooperative learning model on the results of physics learning of students of class VIII MTs Negeri 1 Palu School Year 2021/2022. This type of research is a quasi-experiment with equivalent pretest-posttest design. The population of this study is the entire student of class VIII MTs Negeri 1 Palu. The sampling technique used is proposive sampling with a study sample of class VIII A (n=32) as an experimental class and class VIII B (n=33) as a control class. The data processing results, obtained an average post-test score of the experimental class of 15.25 and a control class of 13.53 from the ideal score of 20.00. Data analysis is done with a two-party test-t statistical technique. The result of the analysis obtained thitung value = 2.55. The value of ttabel = t(0.05)(63) = 2.00 at the real level α = 0.05 and dk = (n1 + n2 – 2) = 32 + 33 -2 = 63. This means, the thitung value is outside the H0 reception area so that H1 is accepted. The results of the data analysis that there is an influence on the use of Powtoon audiovisual-based learning media in cooperative learning models on the results of physics learning of students of Class VIII MTs Negeri 1 Palu.